Reducing incidence of postoperative acute kidney injury in trauma and orthopaedics patients: a quality improvement project. Issue 1 (2nd March 2023) - Kulkarni, Sanat; Richardson, Thomas; Green, Alice; Acharya, Radhika; Latif, Arusa; Johnson, Dakota; Naqvi, Huma; Gella, Sreenadh
Abstract : Background: Acute kidney injury (AKI) is a common postoperative complication which increases morbidity and mortality. This quality improvement project aimed to implement measures targeting known risk factors to decrease the incidence of postoperative AKI in trauma and orthopaedics (T&O) patients. Methods: Data were collected across three six-month to 7-month cycles between 2017 and 2020, analysing all elective and emergency T&O operated patients within a single NHS Trust (n=714, 1008 and 928, respectively). Patients who developed a postoperative AKI were identified using biochemical criteria and data were collected on known AKI risk factors, including use of nephrotoxic medications, and patient outcomes. In the final cycle, the same variables were collected for patients without AKI. Between cycles, measures implemented included: preoperative and postoperative medication reconciliation aiming to stop nephrotoxic medications, orthogeriatrician review of high-risk patients and junior doctor teaching on fluid therapy. Statistical analysis was undertaken to determine the incidence of postoperative AKI across cycles, prevalence of risk factors and impact on length of hospital stay and postoperative mortality. Results: There was a statistically significant decrease in postoperative AKI incidence from 4.27% (43 of 1008 patients) in cycle 2 to 2.05% (19 of 928) in cycle 3 (p=0.006), with a notable decrease in use of nephrotoxic medications. Significant predictors for the development of postoperative AKI included use of diuretics and receiving multiple nephrotoxic drug classes. Development of postoperative AKI significantly increased length of hospital stay by 7.11 days on average (95% CI: 4.84 to 9.38 days, p<0.001) and risk of 1-year postoperative mortality (OR 3.22, 95% CI: 1.03 to 10.55, p=0.046). Conclusion: This project demonstrates that a multifaceted approach targeting modifiable risk factors can reduce incidence of postoperative AKI in T&O patients, which may lead to reduced length of hospital stay and postoperative mortality.